2012
DOI: 10.1111/j.1399-3038.2011.01146.x
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D3 deficiency enhances allergen‐induced lymphocyte responses in a mouse model of allergic airway disease

Abstract: There is debate as to whether vitamin D deficiency contributes towards the extent of the asthma epidemic. In this study, using a mouse model, we determined whether vitamin D deficiency in utero and during early life modulated the severity of asthma. Using dietary restriction, vitamin D(3) -replete and vitamin D(3) -deficient colonies of BALB/c mice were established. Utilizing the allergic airway disease model of asthma with the experimental allergen ovalbumin (OVA), we examined asthma-like responses 24 h after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
59
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(70 citation statements)
references
References 10 publications
10
59
0
1
Order By: Relevance
“…Gorman et al reported that the proliferation and secretion of cytokines in response to OVA in lymph node cells was significantly enhanced by vitamin D deficiency. However, the numbers and proportions of inflammatory cells, cytokines, and the OVA-specific IgE level were not associated with vitamin D deficiency [25]. Vitamin D deficiency was associated with higher bronchial hyperresponsiveness in allergic mouse model than those in vitamin D-sufficient mice.…”
Section: Discussionmentioning
confidence: 80%
“…Gorman et al reported that the proliferation and secretion of cytokines in response to OVA in lymph node cells was significantly enhanced by vitamin D deficiency. However, the numbers and proportions of inflammatory cells, cytokines, and the OVA-specific IgE level were not associated with vitamin D deficiency [25]. Vitamin D deficiency was associated with higher bronchial hyperresponsiveness in allergic mouse model than those in vitamin D-sufficient mice.…”
Section: Discussionmentioning
confidence: 80%
“…We were also unable to assess changes in Th2 cytokines in the BAL as they were below the limits of detection for the method used. Levels of these cytokines may not be easily detected in BAL due to the relatively high dilution with saline, compared with direct measurement of cells in airway-draining lymph nodes (15). Unfortunately, these cells were not collected in this study.…”
Section: Discussionmentioning
confidence: 95%
“…Mechanistically, vitamin D induced protection against airway inflammation has been related to a modulated T cell response to allergens as well as induction of the immunoglobulin-like anti-inflammatory cell surface protein CD200 on T cells, that acts on target immune cells which express the CD200 receptor (CD200R) (Dimeloe et al, 2012; Gorman et al, 2012; Urry et al, 2012). Many authors suggest that the beneficial effect of sufficient vitamin D levels on asthma development results from the immune enhancing effect of vitamin D and the simultaneous prevention of respiratory infections (Ginde et al, 2009; Camargo et al, 2011; Majak et al, 2011; Morales et al, 2012).…”
Section: α25(oh)2d3 and Asthmamentioning
confidence: 99%